2021
DOI: 10.1002/crat.202000209
|View full text |Cite
|
Sign up to set email alerts
|

The Agglomeration of Niacin Crystals in the Cooling Crystallization Process

Abstract: Crystal agglomeration is an important factor that can affect the purity and crystal habit of crystalline products. Agglomeration of niacin crystals in its cooling crystallization and its mechanism is investigated using both experimental and molecular dynamics simulation methods. The magnitude of the interaction energy which is mainly contributed by the hydrogen bond and π–π stacking between the (0 1 1) crystal face and (1 1 −1) crystal face that have both the pyridine and carboxyl groups is the main factor det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In addition, the crystal size increased. Generally, studies have shown that high supersaturation degree can lead to low crystal quality and difficulty in process control. Wang et al found that crystal agglomeration worsened with the increased supersaturation degree, leading to an increase in crystal size and broader distribution. Nonetheless, as illustrated in Figure b, the increase in supersaturation degree did not lead to an increase in the span value.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the crystal size increased. Generally, studies have shown that high supersaturation degree can lead to low crystal quality and difficulty in process control. Wang et al found that crystal agglomeration worsened with the increased supersaturation degree, leading to an increase in crystal size and broader distribution. Nonetheless, as illustrated in Figure b, the increase in supersaturation degree did not lead to an increase in the span value.…”
Section: Resultsmentioning
confidence: 99%